Prevent Mortality Rates of Pregnant Women in Preeclampsia Condition Based on Characteristics Analysis - Rifka Irhamna; Xela Adilla Pramesthi; Yuman Arya Nasrullah; Minarni Wartiningsih (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Background: Preeclampsia is the leading cause of the deaths of pregnant women in Indonesia (30.9%). The cause of preeclampsia until now is not known for sure. The purpose of this study was to determine the characteristics of preeclamptic pregnant women based on age, parity, body mass index and based on a history of hypertension, family history of hypertension, and level of education.Methods: The research method is observasional descriptive. The sampling technique is total sampling. The sample in this study were preeclamptic pregnant women in Dr. Mohammad Soewandhie Hospital in the period of 1 January up to 31 Desember 2017 amounting to 100 samples.Results: The results showed that 55% of preeclampsia pregnant women aged >35 years, 65% of primipaternity preeclampsia mothers, 63% obesity, 67% had no history of hypertension, 78% had no family history of hhypertension, and level of education does not affect the condition.Conclusions and Discussions: The highest risk factors for preeclampsia are age> 35 years, primipaternity and obesity. Therefore, it needs appropriate prevention methods to avoid the emergence of pregnancy problems and their complications include recognizing the signs and symptoms of preeclampsia, be aware of risk factors for the causes of preeclampsia, routine antenatal care, and adopting a healthy lifestyle.